2012
DOI: 10.1177/1049732312443427
|View full text |Cite
|
Sign up to set email alerts
|

African American and Non-African American Patients’ and Families’ Decision Making About Renal Replacement Therapies

Abstract: We conducted focus group meetings of African American and non-African American patients with end-stage renal disease (six groups) and their family members (six groups), stratified by race/ethnicity and treatment. We elicited differences in participants’ experiences with shared decision making about initiating renal replacement therapy (RRT; that is, hemodialysis, peritoneal dialysis, or a kidney transplant). Patients were often very sick when initiating RRT, and had little, if any, time to make a decision abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
56
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 25 publications
0
56
0
2
Order By: Relevance
“…This is an important finding because past work[40, 41] has shown that patients who are well-informed about transplant are more likely to be interested in pursuing it, suggesting that some of the reluctance to pursue transplant expressed by our participants may have stemmed from a lack of knowledge and from ineffective doctor-patient communication, not just from a lack of trust. Thus, our findings highlight the need to ensure that patients are receiving accurate information about the risks and benefits of transplant, and that clinicians have the time and training to engage effectively in discussions with patients around transplant preferences.…”
Section: Discussionmentioning
confidence: 64%
“…This is an important finding because past work[40, 41] has shown that patients who are well-informed about transplant are more likely to be interested in pursuing it, suggesting that some of the reluctance to pursue transplant expressed by our participants may have stemmed from a lack of knowledge and from ineffective doctor-patient communication, not just from a lack of trust. Thus, our findings highlight the need to ensure that patients are receiving accurate information about the risks and benefits of transplant, and that clinicians have the time and training to engage effectively in discussions with patients around transplant preferences.…”
Section: Discussionmentioning
confidence: 64%
“…Second, because 73% of patients with ESRD receive regular in-center dialysis treatments in approximately 6000 centers in the United States (1), systematized education within this setting can provide a much needed opportunity to educate more patients with ESRD about LDKT, including those who have not yet presented to a transplant center for evaluation. Third, ensuring that comprehensive LDKT education occurs within dialysis centers may help to reduce known ethnic or racial disparities in access to transplant education (7,8) and LDKT (9) by teaching these patients about their option for LDKT and about the steps needed to begin evaluation or seek living donors. Fourth, although positive messages about donating kidneys upon death are available to the general public (10), misinformation about LDKT still remains and can be exacerbated by inaccurate media portrayals (11).…”
Section: Introductionmentioning
confidence: 99%
“…6 Although the US government mandates that all ESRD patients receive education about kidney transplant, 7 current research suggests that at least 30% of dialysis patients are uninformed about this option. 8 Further, research has shown that health care providers are often unable to educate patients about transplant because of their own lack of knowledge or time constraints.…”
mentioning
confidence: 99%